Integrating Tolerance and Religious Moderation in Sharia Education at Politeknik Negeri Medan - Gunawan; Nasrudin; Parma Hadi Rantelinggi (PT ARFA DIGITAL TECHNOLOGY, 2025)
This study seeks to examine how the values of tolerance and religious moderation are integrated into the process of Sharia education at Politeknik Negeri Medan. In the context of increasing challenges to diversity and the potential rise of radicalism within higher education institutions, this research emphasizes the importance of Sharia-based learning that promotes inclusivity, dialogue, and respect for differences. The study employed a qualitative approach, with data collected through interviews, observations, and document studies involving lecturers, students, and curricula related to Islamic studies courses. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Politeknik Negeri Medan has implemented the values of religious moderation in Sharia education through several strategies, including the strengthening of materials on wasathiyyah (Islamic moderation), the application of dialogical learning methods, and religious activities that foster a sense of togetherness among students from diverse backgrounds. However, the study also found a need to enhance lecturers’ capacity to integrate tolerance values more explicitly into teaching materials and learning evaluations. The study concludes that integrating Sharia education with the values of tolerance and religious moderation plays a crucial role in shaping students’ character to be ethical, open-minded, and adaptive to diversity. The research recommends the development of an Islamic curriculum based on maqāṣid al-syarī‘ah that focuses on nurturing a generation of moderate Muslims.